Lanthanide Structures, Coordination, and Extraction Investigations of a 1,3-Bis(diethyl amide)-Substituted Calix[4]arene Ligand. - Beer, P; Drew, MG; Kan, M; Leeson, P; Ogden, M; Williams, G (1996)
The synthesis and structure determinations of lanthanum, samarium, ytterbium, and lutetium complexes of 5,11,17,23-tetra-tert-butyl-25,27-bis((diethylcarbamoyl)methoxy)-26,28-dihydroxycalix[4]arene (L) are described. The four structures display similar characteristics with the trivalent lanthanide cation being encapsulated in an eight-coordinate oxygen environment, consisting of six oxygens from the calixarene, a water molecule, and unidentate picrate for lanthanum [La(L-2H)(picrate)(H(2)O)]; and bidentate chelating picrate for the other lanthanides [Ln(L-2H)(picrate)]Ln = Sm, Yb, Lu. Under optimised experimental conditions solvent extraction investigations showed the calix[4]arene ligand L exhibited generally very high percentage extractabilities of lanthanide cations into dichloromethane, presumably on account of the ligand's unique lower rim oxygen containing coordination sphere and its lipophilic exterior.